Isi kandungan kontrak : klasifikasi terma dan permasalahannya - Sakina Shaik Ahmad Yusoff (Fakulti Undang - Undang, 2001)

(untitled)
The terms of the contract are its heart and life-blood in that they define both the content and scope of the parties’ mutual rights and obligations. Classification of terms has brought about several unresolved problems. Classically, terms of the contract have been divided into either conditions or warranties. The development of the innominate term introduces a more logical flexibility. A balance has to be struck between the two approaches; certainty brought about by the classical approach and flexibility as potrayed by the modern approach. Combining both approaches allows the court to tread a middle-path between rigid and unjust rule an one side, and indeterminate flexibility on the other. Terms have also been classified as express or implied. A court may be required to imply a term if the parties have specified only the rudimentary obligations. The duty of a court to find the existence of an implied term in a contract nevertheless is a matter to be exercised with care. In implying terms into contracts, what criterion would be a more appropriate rubric to adopt? Implied terms also raises questions of its status vis-à-vis the express terms of a contract. This article is thus devoted to analyzing some problems brought about by the classification of contractual terms and looks at some thoughts surrounding these problems